Analisis Kemantapan Jalan Kayuagung-Pedamaran Timur dengan Metode IRI Menggunakan Aplikasi RoadBump Pro: Stability Analysis of Kayuagung-Pedamaran Timur Road with IRI Method Using RoadBump Pro Application - Muslikah, Siti; Yuliana, Idaya (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
Steady and stable roads are needed to distribute goods and services smoothly. It is necessary to check the performance of the road network on a regular basis for planning effective and efficient road improvements. The level of road flatness (International Roughness Index, IRI) is one of the service factors/functional performance of a pavement that greatly influences the driver's comfort (riding quality). One of the smartphone applications to get road IRI scores is Roadbump Pro. The results of the assessment of the Kayuagung-Pedamaran Timur (Jalan Sebuku) road using IRI based on the Roadbump Pro application, mostly include unstable roads, and road improvement efforts that must be carried out are road improvements. Meanwhile, based on the type of vehicle used, the measurement of the IRI value based on the RoadBump Pro application is smaller if using an SUV vehicle than using a pickup vehicle. The level of road flatness (International Roughness Index, IRI) is one of the service factors/functional performance of a pavement that greatly influences the driver's comfort (riding quality). One of the smartphone applications to get road IRI scores is Roadbump Pro. The results of the assessment of the Kayuagung-Pedamaran Timur (Jalan Sebuku) road using IRI based on the Roadbump Pro application, mostly include unstable roads, and improvement efforts must be carried out. Meanwhile, based on the type of vehicle used, the measurement of the IRI value based on the RoadBump Pro application is smaller if using an SUV vehicle than using a pickup vehicle.